PROXIMATE COMPOSITION OF BROWN SEAWEED (Sargassum ilicifolium - M.Faisal Saputra S; Edison Edison; Andarini Diharmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTOne type of brown seaweed Sargassumilicifolium can be used as a source of food, pharmaceuticals, and cosmetics. This study aims to determine the composition of the proximate Sargassumilicifolium. The research method used is an experiment with experiments on S. ilicifolium by analyzing the proximate composition consisting of moisture, ash, fat, and carbohydrate content by difference. The results of the analysis showed that S.ilicifolium had moisture content of 14.73% (dw), ash 20.03% (dw), fat 1.12% (dw), protein 7.35% (dw) and carbohydrates (by difference) 72.11% (dw). Sargassumilicifolium is a relatively high source of minerals and carbohydrates and protein for this type of seaweed.Keywors: analysis, carbohydrate, mineral, seaweed